2015
DOI: 10.3109/00365548.2014.987163
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of biomarkers for distinguishing between bacterial and viral etiologies in pediatric lower respiratory tract infections

Abstract: The combined analysis improved diagnostic accuracy in children with bacterial and viral LRTIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…The majority of these patients had clinical diagnosis of acute upper respiratory tract infection, pneumonia and acute gastroenteritis. This indicates absence of bacterial cause similar to published data from previous studies [7, 30, 31]. In these cases, clinicians should consider not to treat the child with antimicrobial drugs.…”
Section: Discussionsupporting
confidence: 89%
“…The majority of these patients had clinical diagnosis of acute upper respiratory tract infection, pneumonia and acute gastroenteritis. This indicates absence of bacterial cause similar to published data from previous studies [7, 30, 31]. In these cases, clinicians should consider not to treat the child with antimicrobial drugs.…”
Section: Discussionsupporting
confidence: 89%
“…CD35 is a membrane-bound complement regulator, and CD64 is an integral membrane glycoproteins of white blood cells. Both CD35 and CD64 are present at higher levels in children with bacterial versus viral lower respiratory tract infections [ 51 ]. In addition, presepsin, an immunologic biomarker related to bacterial phagocytosis, specifically elevates in response to bacterial infections [ 52 ].…”
Section: Bacterial Protein Biomarkersmentioning
confidence: 99%
“…The combined triple host protein assay comprising TRAIL, IP-10, and CRP for distinguishing between bacterial and viral infections is superior to single-biomarker methods [ 4 , 15 , 25 , 63 ], and has 93.5% sensitivity and 94.3% specificity [ 25 ]. Another approach using combinations of CRP + CD35 and CRP + CD64 was found to provide better discriminative power than a single biomarker or CRP + PCT and CRP + IL-6 for the differentiation of bacterial and viral lower respiratory tract infections in children [ 51 ]. Although some studies found that combined assessment did not improve assay results [ 64 ], combined approaches offer several promising possible avenues for improved diagnostic differentiation.…”
Section: Biomarker Combinationsmentioning
confidence: 99%
“…Although, in most cases, a combination of traditional biomarkers, including WBC count, NP, ESR, CRP, and PCT, has been found to be poorly effective—or not at all effective—in increasing the sensitivity and specificity of a single biomarker [40], it has been presumed that combining new biomarkers with one or more of the traditionally used variables may yield better results. A positive example in this regard comes from a study by Erdman et al [41], who have investigated children with World Health Organization (WHO)-defined clinical CAP [42] and have found that the combined evaluation of CRP and chitinase 3-like-1, a soluble glycoprotein induced by cytokines and injurious stimuli [43] discriminated between end-point CAP and non-end-point CAP with 93% sensitivity (95% CI 76.5–98.8), 80.8% specificity (95% CI 72.6–87.1), a positive likelihood ratio of 4.9 (95% CI 3.4–7.1), a negative likelihood ratio of 0.083 (0.022–0.32), and a misclassification rate of 0.20 (standard error of 0.038).…”
Section: Differentiation Of Bacterial From Viral Capmentioning
confidence: 99%